Pd‐Porphyrin‐Cross‐Linked Implantable Hydrogels with Oxygen‐Responsive Phosphorescence. Issue 6 (20th November 2013) - Huang, Haoyuan; Song, Wentao; Chen, Guanying; Reynard, Justin M.; Ohulchanskyy, Tymish Y.; Prasad, Paras N.; Bright, Frank V.; Lovell, Jonathan F.
<x xml:space="preserve">Abstract</x> Development of long‐term implantable luminescent biosensors for subcutaneous oxygen has proved challenging due to difficulties in immobilizing a biocompatible matrix that prevents sensor aggregation yet maintains sufficient concentration for transdermal optical detection. Here, Pd‐porphyrins can be used as PEG cross‐linkers to generate a polyamide hydrogel with extreme porphyrin density (≈5 × 10−3m). Dye aggregation is avoided due to the spatially constraining 3D mesh formed by the porphyrins themselves. The hydrogel exhibits oxygen‐responsive phosphorescence and can be stably implanted subcutaneously in mice for weeks without degradation, bleaching, or host rejection. To further facilitate oxygen detection using steady‐state techniques, an oxygen‐non‐responsive companion hydrogel is developed by blending copper and free base porphyrins to yield intensity‐matched luminescence for ratiometric detection.